Bulgeless galaxies in the COSMOS field: environment and star formation evolution at z < 1. Issue 1 (8th December 2017) - Grossi, Marco; Fernandes, Cristina A C; Sobral, David; Afonso, José; Telles, Eduardo; Bizzocchi, Luca; Paulino-Afonso, Ana; Matute, Israel
Abstract: Combining the catalogue of galaxy morphologies in the COSMOS field and the sample of H α emitters at redshifts z = 0.4 and z = 0.84 of the HiZELS survey, we selected ∼ 220 star-forming bulgeless systems (Sérsic index n ≤ 1.5) at both epochs. We present their star formation properties and we investigate their contribution to the star formation rate function (SFRF) and global star formation rate density (SFRD) at z < 1. For comparison, we also analyse H α emitters with more structurally evolved morphologies that we split into two classes according to their Sérsic index n : intermediate (1.5 < n ≤ 3) and bulge-dominated ( n > 3). At both redshifts, the SFRF is dominated by the contribution of bulgeless galaxies and we show that they account for more than 60 per cent of the cosmic SFRD at z < 1. The decrease of the SFRD with redshift is common to the three morphological types, but it is stronger for bulge-dominated systems. Star-forming bulgeless systems are mostly located in regions of low to intermediate galaxy densities (Σ ∼ 1–4 Mpc −2 ) typical of field-like and filament-like environments and their specific star formation rates (sSFRs) do not appear to vary strongly with local galaxy density. Only few bulgeless galaxies in our sample have high (sSFR > 10 −9 yr −1 ) and these are mainly low-mass systems. Above M * ∼ 10 10 M⊙ bulgeless are evolving at a 'normal' rate (10 −9 yr −1 < sSFR < 10 −10 yr −1 ) and in the absence of an external trigger (i.e. mergers/strong interactions) they might not be able to develop a central classical bulge.